Managing Teachers Barriers in Usage Of ICT in Education at Smart Schools in Selangor : Towards Developing Digital School Resource Centers - Jaswant Singh, Shilinder Kaur (2014)
Information and Communications Technology (ICT) have created a new global economy “powered by technology, fuelled by information and driven by knowledge”. Globalization and Technology changes have brought a significant impact on the education sector or institutions worldwide including Malaysia. Regarding to this phenomenon in Malaysia, The Ministry of Education has put much effort in funding, training the teachers and students as well as the schools to equip them with ICT skills and appliances. There is no doubt that ICT benefits in helping our education system to be more effective as modernization of other developed countries. Many issues have been raised regarding the implementation of ICT in teaching and learning in our Malaysian school. An ICT role gives us the advantages for example, update pedagogical approaches to e-learning and teaching and offers access to a lot of data and information, and thus can create a new interesting way of learning. The integration of information and communication technology (ICT) in teaching and learning provides more opportunities for teachers and students to work better in an information age. However, some barriers may discourage teachers to integrate ICT in the classroom and prevent them to introduce supporting materials through ICT usage. Examining the barriers for using ICT in education can assist the educators to overcome the obstacles and integrate the ICT in everyday education. This study aims to investigate the teachers’ perceptions of the barriers and challenges preventing teachers to integrate ICT in the classroom.